Climate change and impacts on family farming in the North and Northeast of Brazil - Haroldo Machado Filho; Cássia Moraes; Paula Bennati; Renato de Arag\~ao Rodrigues; Marcela Guilles; Pedro Rocha; Amanda Lima; Isadora Vasconcelos (International Policy Centre for Inclusive Growth (IPC-IG), 2016)
The starting point for this study was the consideration of future climate change scenarios and their uncertainties. The paper presents the global projections from the Intergovernmental Panel on Climate Change (IPCC) Fifth Assessment Report (AR5) and compares them with regional scenarios (downscaling) developed by the Brazilian National Institute for Space Research (Instituto Nacional de Pesquisas Espaciais-INPE), with a focus on two main IPCC scenarios (RCP4.5 and RCP8.5) and two main global models (MIROC and Hadley Centre) for the periods 2011-2040 and 2041-2070. It aims to identify the main trends in terms of changes in temperature and precipitation for the North and Northeast regions of Brazil (more specifically, in the Amazon, semi-arid and cerrado biomes). [...]
Keywords: 330; climate change; impacts; family farming; North; Northeast; Brazil